2023
DOI: 10.1021/acscatal.3c03788
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Cobalt Bis(Benzylaminedithiolate) to Reduced Graphene Oxide as a Thin-Film Electrocatalyst for Hydrogen Production with Remarkable Dioxygen Tolerance

Virginia A. Larson,
Nicolai Lehnert

Abstract: Hydrogen (H2) can be produced in the water splitting reaction, specifically on the cathodic side through the hydrogen evolution reaction (HER), where two protons and two electrons are combined to make H2. Herein, we report a molecular catalyst, [cobalt bis­(benzylammoniumdithiolate)]+, covalently attached to graphene oxide (GO) as a thin-film catalyst for HER. A member of the acclaimed cobalt dithiolene family of HER catalysts, this complex was characterized by UV–vis and paramagnetic 1H NMR spectroscopy, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Previously, others and ourselves have shown that Co bis(benzenedithiolate) type complexes are highly active catalysts for the Hydrogen Evolution Reaction (HER). This includes homogenous electrocatalytic HER [1], homogeneous photocatalytic HER [1,2], and heterogeneous HER when either physisorbed to electrode surfaces [3][4][5], as active sites in MOFs [6][7][8][9], or, as recently reported, when covalently attached to an electrode surface [10]. These catalysts perform well in HER compared to other heterogenized earth-abundant transition-metal molecular complexes that have been reported in the literature [10][11][12].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Previously, others and ourselves have shown that Co bis(benzenedithiolate) type complexes are highly active catalysts for the Hydrogen Evolution Reaction (HER). This includes homogenous electrocatalytic HER [1], homogeneous photocatalytic HER [1,2], and heterogeneous HER when either physisorbed to electrode surfaces [3][4][5], as active sites in MOFs [6][7][8][9], or, as recently reported, when covalently attached to an electrode surface [10]. These catalysts perform well in HER compared to other heterogenized earth-abundant transition-metal molecular complexes that have been reported in the literature [10][11][12].…”
Section: Introductionmentioning
confidence: 77%
“…This includes homogenous electrocatalytic HER [1], homogeneous photocatalytic HER [1,2], and heterogeneous HER when either physisorbed to electrode surfaces [3][4][5], as active sites in MOFs [6][7][8][9], or, as recently reported, when covalently attached to an electrode surface [10]. These catalysts perform well in HER compared to other heterogenized earth-abundant transition-metal molecular complexes that have been reported in the literature [10][11][12]. However, Co bis(benzenedithiolate) type complexes are often shown to decline in activity over time [4,5,10].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations